Literacy Practices in EFL Context: Insights from English Teachers in Rural Areas of Maluku - Felicia Miranda Lekatompessy; Jeny Lekatompessy; Jusak Patty (Huele: Journal of Applied Linguistics, Literature and Culture, 2026)
Literacy practices in EFL contexts within geographically marginalized regions remain understudied, particularly in eastern Indonesia. This study examined how English teachers in rural areas of the Aru Islands Regency, Tual City, and Southeast Maluku Regency enact literacy practices in their classrooms. A mixed-methods explanatory sequential design was employed, with quantitative data collected through an adapted PISA 2018 Language Teacher Questionnaire administered to 19 teachers, followed by semi-structured Zoom interviews with five participants to deepen the survey findings. Descriptive and thematic analyses revealed that teachers demonstrated meaningful commitment to students' literacy development through pre-lesson reading routines, vocabulary enrichment tasks, and integration of digital tools such as Canva and Quizizz. Nevertheless, most teachers held a narrow view of literacy, associating it predominantly with reading skills. Limited infrastructure and students' declining reading motivation posed persistent challenges. Future research should incorporate students' perspectives to provide a more comprehensive account of literacy outcomes.